Heterogenität der Beschäftigungsdynamik und~Segmentierungsphänomene auf dem deutschen Arbeitsmarkt - Bernhard Boockmann; Susanne Steffes (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
– This paper presents recent empirical evidence on the extent and determinants of employment dynamics and job mobility, building on economic theory and German labor market institutions. In particular, it identifies dynamic and immobile segments of the labor market. Conclusions are drawn with respect to companies' personnel policies, as well as to public policy aimed at integrating the unemployed into stable employment relationships.
Keywords: J21; J23; J31; J38; 330; Arbeitsplatzwechsel; labour turnover; zwischenbetriebliche Mobilität - Determinanten; institutionelle Faktoren; Arbeitsmarktpolitik; Arbeitsmarktsegmentation; Personalpolitik; Arbeitsmarkt - Flexibilität; IAB-Linked-Employer-Employee-Datensatz; Beschäftigungsdauer - Determinanten; Konjunkturzyklus; Mütter; Berufsrückkehrerinnen; Weiterbildungsangebot; Beruf und Familie